IV thrombolysis in very severe and severe ischemic stroke: Results from the SITS-ISTR Registry. (15th December 2015) - Mazya, Michael V.; Lees, Kennedy R.; Collas, David; Rand, Viiu-Marika; Mikulik, Robert; Toni, Danilo; Wahlgren, Nils; Ahmed, Niaz
Abstract : Objective: To study the safety of off-label IV thrombolysis in patients with very severe stroke (NIH Stroke Scale [NIHSS] scores >25) compared with severe stroke (NIHSS scores 15–25), where treatment is within European regulations. Methods: Data were analyzed from 57, 247 patients with acute ischemic stroke receiving IV tissue plasminogen activator in 793 hospitals participating in the Safe Implementation of Thrombolysis in Stroke (SITS) International Stroke Thrombolysis Registry (2002–2013). Eight hundred sixty-eight patients (1.5%) had NIHSS scores >25 and 19, 995 (34.9%) had NIHSS scores 15–25. Outcome measures were parenchymal hemorrhage, symptomatic intracerebral hemorrhage, mortality, and functional outcome. Results: Parenchymal hemorrhage occurred in 10.7% vs 11.0% ( p = 0.79), symptomatic intracerebral hemorrhage per SITS-MOST (SITS–Monitoring Study) in 1.4% vs 2.5% ( p = 0.052), death at 3 months in 50.4% vs 26.9% ( p < 0.001), and functional independence at 3 months in 14.0% vs 29.0% ( p < 0.001) of patients with NIHSS scores >25 and NIHSS scores 15–25, respectively. Multivariate adjustment did not change findings from univariate comparisons. Posterior circulation stroke was more common in patients with NIHSS scores >25 (36.2% vs 7.4%, p < 0.001), who were also more often obtunded or comatose on presentation (58.4% vs 7.1%, p < 0.001). Of patients with NIHSS scores >25, 26.2% were treated >3 hours from symptom onset vs 14.5% with NIHSS scores of 15–25. Conclusions: Our data show no excess risk of cerebral hemorrhage in patients with NIHSS score >25 compared to score 15–25, suggesting that the European contraindication to IV tissue plasminogen activator treatment at NIHSS levels >25 may be unwarranted. Increased mortality and lower rates of functional independence in patients with NIHSS score >25 are explained by higher stroke severity, impaired consciousness on presentation due to posterior circulation ischemia, and longer treatment delays.